Creation and Implementation of an Environmental Scan to Assess Cancer Genetics Services at Three Oncology Care Settings. Issue 6 (16th May 2018) - Bednar, Erica M.; Walsh, Michael T.; Baker, Ellen; Muse, Kimberly I.; Oakley, Holly D.; Krukenberg, Rebekah C.; Dresbold, Cara S.; Jenkinson, Sandra B.; Eppolito, Amanda L.; Teed, Kelly B.; Klein, Molly H.; Morman, Nichole A.; et al.
Abstract: An environmental scan (ES) is an efficient mixed‐methods approach to collect and interpret relevant data for strategic planning and project design. To date, the ES has not been used nor evaluated in the clinical cancer genetics setting. We created and implemented an ES to inform the design of a quality improvement (QI) project to increase the rates of adherence to national guidelines for cancer genetic counseling and genetic testing at three unique oncology care settings (OCS). The ES collected qualitative and quantitative data from reviews of internal processes, past QI efforts, the literature, and each OCS. The ES used a data collection form and semi‐structured interviews to aid in data collection. The ES was completed within 6 months, and sufficient data were captured to identify opportunities and threats to the QI project's success, as well as potential barriers to, and facilitators of guideline‐based cancer genetics services at each OCS. Previously unreported barriers were identified, including inefficient genetic counseling appointment scheduling processes and the inability to track referrals, genetics appointments, and genetic test results within electronic medical record systems. The ES was a valuable process for QI project planning at three OCS and may be used to evaluate genetics services in other settings.